APERSEPSI MAHASISWA TERHADAP PENDIDIKAN ORANG DEWASA DALAM PEMBELAJARAN DI PERGURUAN TINGGI - Abdul Istiqlal; Afdhal Rinsik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2021)
This research was to describe the upperception student at adult learners in learning at High school (STKIP Ahlussunannah bukittinggi). This research is gualitataive descriptive research. The infomance research 26 student, and 1 lecture. It is aimed that the adult learners will have several skills, such as problem solving, dicision making, critical and creative thinking. By having so hopefully the learners can create their own and way of life increasingly. Besides,the will be able to optimize their creativities in their every day life as adult in their society. This research can describe 62 % student understand the upperception for adult learning at high school. Theirs can different basic school and middle school by high education. In the high education, student active to learns in learning process. Theirs to learning and an adult commonly likes for having his personality type an activator. The personality type as an activator prefers to have a concise information and logic without any recommendation for another act. The ended, their student to give and motivation explanation together wit the impacts that will be faced by human beings and learning at higher education.